Fractional anisotropy in the posterior limb of the internal capsule and prognosis in amyotrophic lateral sclerosis. - Menke, R; Abraham, I; Thiel, C; Filippini, N; Knight, S; Talbot, K; Turner, M (2012)
OBJECTIVE: To explore the value of diffusion tensor imaging applied to those specific cerebral white matter tracts consistently involved pathologically in amyotrophic lateral sclerosis as a source of prognostic biomarkers. DESIGN: Baseline clinical assessment and 3-T diffusion tensor imaging, repeated after approximately 6 months.Tract-based spatial statistics were used to assess voxel wise correlations of just the baseline diffusion tensor imaging indices with the progression rate (change in disability score/time interval) within the corticospinal tract and corpus callosum. PATIENTS: The study involved 21 patients with amyotrophic lateral sclerosis and 3 patients with primary lateral sclerosis. RESULTS: Correlation was observed between fractional anisotropy and progression rate for a region of the corticospinal tract spanning the posterior limb of the internal capsule, with a left hemisphere emphasis. Posterior limb of the internal capsule fractional anisotropy showed potential to distinguish those patients with rapid progression. Axial diffusivity significantly increased in this region in a paired t test analysis of baseline and follow-up diffusion tensor imaging, in keeping with axonal damage.No correlations were noted for the corpus callosum. CONCLUSIONS: Posterior limb of the internal capsule fractional anisotropy is a candidate prognostic marker in amyotrophic lateral sclerosis, with potential to identify incident cases with more rapid progression.